Tinjauan MaqᾹṣid Syarī‘Ah Terhadap Pembekuan Sperma (Sperm Freezing) dalam Proses Bayi Tabung - Tajul Iflah; Raihan Putri (Fakultas Syariah IAIN Laa Roiba Bogor, 2024)
In vitro fertilization is a solution for anyone who wants to have offspring if one of them is infertile or is caused by another disease. One of the creations of today's human sophistication is artificial insemination or what is called test tube babies. Technological advances have made it possible to carry out scientific and technological endeavors. This Ḥifẓ an-nasl is one of the goals of Maqāṣid asy-Syarīʿah, test tube babies are an effort to maintain offspring so that their offspring are not interrupted. Even though it is a solution, In vitro fertilization is also vulnerable to abuse so it has the potential to have a negative impact if misused. This research was conducted to find out how the legal aspects of long-term sperm freezing for test tube babies are reviewed according to Maqāṣid asy-Syarīʿah. This research uses a historical approach method by looking at events or phenomena carried out by married couples with the aim of obtaining offspring. The results of the research show that freezing sperm cells is carried out with the aim of being able to obtain offspring for married couples who can no longer produce offspring and sperm cells have been frozen when the husband and wife are still in a fertile state. This is legally permitted in Islam with the provisions that the sperm must come from the husband and wife who has a legal marriage relationship. If it is related to Maqāṣid ash-Syarīʿah, the existence of a sperm bank for freezing can protect offspring or ḥifẓ an-nasl, then in Islam it is permissible because this action has benefits in it. Sperm freezing is permitted provided there is a real problem and it is safe from misuse.